2002
DOI: 10.1002/jmor.10045
|View full text |Cite
|
Sign up to set email alerts
|

Development of the supraorbital and mandibular lateral line canals in the cichlid, archocentrus nigrofasciatus

Abstract: The development of two of the cranial lateral line canals is described in the cichlid, Archocentrus nigrofasciatus. Four stages of canal morphogenesis are defined based on histological analysis of the supraorbital and mandibular canals. "Canal enclosure" and "canal ossification" are defined as two discrete stages in lateral line canal development, which differ in duration, an observation that has interesting implications for the ontogeny of lateral line function. Canal diameter in the vicinity of individual ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(81 citation statements)
references
References 41 publications
6
74
0
1
Order By: Relevance
“…Neuromasts can be found on the entire body surface including the tail with the cupulae extending into the water (Schellart & Wubbels, 1998;Eastman & Lannoo, 2003;Tarby and Webb, 2003;Sane et. al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Neuromasts can be found on the entire body surface including the tail with the cupulae extending into the water (Schellart & Wubbels, 1998;Eastman & Lannoo, 2003;Tarby and Webb, 2003;Sane et. al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the association may be essential, if the formation of dermal bones and of canals both depend on a single initiation event ("onecomponent" view). Dermal bones and canal walls were shown to derive from a single ossification center in a species with many derived characters, leading to the hypotheses that the "one-component" development is a derived feature (Tarby and Webb 2003).…”
Section: Growth In 3d: Canals and Bonesmentioning
confidence: 99%
“…This observation constitutes a preliminary finding that requires further substantiation. Previous reports [Coombs et al, 1989;Tarby and Webb, 2003] suggested that the development of canal neuromasts is subordinate to the mechanical limits set by the growth of the dermal bone. Accordingly, it was not surprising to notice that, as observed in Cottidae [Janssen et al, 1987] and Cichlidae [Münz, 1989;Tarby and Webb, 2003], the size of canal neuromasts was positively correlated with fish size.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports [Coombs et al, 1989;Tarby and Webb, 2003] suggested that the development of canal neuromasts is subordinate to the mechanical limits set by the growth of the dermal bone. Accordingly, it was not surprising to notice that, as observed in Cottidae [Janssen et al, 1987] and Cichlidae [Münz, 1989;Tarby and Webb, 2003], the size of canal neuromasts was positively correlated with fish size. Consequently, and in agreement with Coombs et al [1989] and Webb [1989b], the size of superficial neuromasts, which are free from morphological constraints, presents a wide range of values and, at the same time, their number increases with fish size [Blaxter et al, 1983;Blaxter, 1987;Prié-Granié;Harvey et al, 1992;Higgs and Fuiman, 1996;Appelbaum and Riehl, 1997;Poling and Fuiman, 1997;Webb and Shirey, 2003].…”
Section: Discussionmentioning
confidence: 99%